2000
DOI: 10.1038/sj.sc.3101031
|View full text |Cite
|
Sign up to set email alerts
|

Sitting position–Posture and performance in C5–C6 tetraplegia

Abstract: Objectives: To investigate how sitting position and seating aect posture and performance (balance, transfers, wheelchair skills, physical strain during wheelchair propulsion, spasticity and respiration) in persons with C5 and C6 tetraplegia. Setting: Outpatient clinic`SpinalhaÈ lsan', GoÈ teborg, Sweden. Method: Baseline measurements of sitting position and performance were performed followed by an intervention period. The intervention was individually adapted to each person with emphasis on reduction of kypho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 13 publications
0
31
0
4
Order By: Relevance
“…Lower backrests allow for greater freedom of upper extremity movement. 18,19 Further, headrest is necessary if the patient does not have enough neck control and has an upper level of cervical SCI. 2 Although it was required, only one patient did not have headrest in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Lower backrests allow for greater freedom of upper extremity movement. 18,19 Further, headrest is necessary if the patient does not have enough neck control and has an upper level of cervical SCI. 2 Although it was required, only one patient did not have headrest in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the effect of wheelchair configurations or seating systems on reach and UE functional tasks. These studies found results differed depending on the task and the configuration used in the study (2,7,15,18,(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have used skin-mounted markers on ASIS, trochanter major, and vertical and horizontal lines. 30 Myhr and von Wendt 31 analyzed video films and photographs of children with cerebral palsy in different sitting positions. In order to calculate angles on photographs, anatomical landmarks were used and a line drawn vertically through the landmark of trochantor major was used to define the fulcrum.…”
Section: Introductionmentioning
confidence: 99%